METODE PEMBELAJARAN NABI IBRAHIM AS DALAM PRESPEKTIF AL-QUR’AN - hafidh nur fauzi (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2019)
Abstract: Education is one component that is very necessary to shape the human personality. One of the study materials in education is the stories in the Koran laden with wisdom and wisdom that will not be exhausted until ever, eternal examples are exemplified in figures narrated in the Koran, one of which is the figure of Nabiyullah Ibrahim AS. in the world of child education, methods are very important in education, because methods are the initial foundation for achieving an educational goal and the principle of success in learning. If the method is used well then the results will have an impact on the quality of education that is good, but if the method used is not good then the results will also result in the quality of learning that will not be good either. An educator should give full attention to both methods in general methods and specific methods in teaching in order to achieve success which is the goal of education. Keywords: Learning Methods, Nabi Ibrahim, al-Qur'an